2004
DOI: 10.1074/jbc.m310997200
|View full text |Cite
|
Sign up to set email alerts
|

Deactylase Inhibitors Disrupt Cellular Complexes Containing Protein Phosphatases and Deacetylases

Abstract: Affinity isolation of protein serine/threonine phosphatases on the immobilized phosphatase inhibitor microcystin-LR identified histone deacetylase 1(HDAC1), HDAC6, and HDAC10 as novel components of cellular phosphatase complexes. Other HDACs, specifically HDAC2, -3, -4, and -5, were excluded from such complexes. In vitro biochemical studies showed that recombinant HDAC6, but not HDAC4, bound directly to the protein phosphatase (PP)1 catalytic subunit. No association was observed between HDAC6 and PP2A, another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 51 publications
5
103
2
Order By: Relevance
“…Recombinant HDAC6 binds directly to protein phosphatase 1 (PP1) catalytic subunit. TSA disrupts endogenous HDAC6-PP1 complexes (Brush et al, 2004). HDAC1 and 10 are also components of cellular phosphatase complexes.…”
Section: Ros Thioredoxin and Trx Binding Protein 2 Inmentioning
confidence: 99%
“…Recombinant HDAC6 binds directly to protein phosphatase 1 (PP1) catalytic subunit. TSA disrupts endogenous HDAC6-PP1 complexes (Brush et al, 2004). HDAC1 and 10 are also components of cellular phosphatase complexes.…”
Section: Ros Thioredoxin and Trx Binding Protein 2 Inmentioning
confidence: 99%
“…However, at least one report shows that both proteins interact with the major cellular phosphatase, PP1, and could therefore be involved in the same regulatory networks (Brush et al, 2004). A very recent study also led to the identification of two factors involved in the pre-mRNA 3 0 -end processing, the cleavage factor CFIm25 and poly-A polymerase, as in vivo HDAC10 substrates, suggesting a probable function for this protein in the regulation of the 3 0 -end processing machinery (Shimazu et al, 2007).…”
Section: An Hdac6-related Deacetylase Hdac10mentioning
confidence: 99%
“…These findings indicate that TSA negatively affects lymphocyte extravasation, mainly their firm adhesion to endothelium under flow stress conditions, an effect that is not evident under static conditions. This could be due to blockage of deacetylase activity and/or disruption of HDAC6 molecular complexes by TSA (Brush et al, 2004).…”
Section: Lymphocyte Transmigration Inhibition By Hdac6mentioning
confidence: 99%
“…TSA is a broad HDACs inhibitor, whereas tubacin is specific for the tubulin deacetylase activity of HDAC6 (Hubbert et al, 2002;Matsuyama et al, 2002;Haggarty et al, 2003;Zhang et al, 2003). These compounds inhibit the HDAC6 deacetylase activity by chelating a Zn 2ϩ cation (Furumai et al, 2001;Jose et al, 2004) and may also alter the formation of dynamic molecular complexes of HDAC6 with other intracellular proteins such PP1, HSP90, Dia2, dynein, or tubulin (Kawaguchi et al, 2003;Brush et al, 2004;Destaing et al, 2005;Hideshima et al, 2005;Kovacs et al, 2005). In this regard, it has been reported that TSA disrupts HDAC6/PP1 association, affecting the enzymatic activity of both molecules (Brush et al, 2004).…”
Section: Introductionmentioning
confidence: 99%